Evaluation of Antibiotic Resistance Patterns and Biofilm Formation among the Clinical Isolates of Pseudomonas aeruginosa (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To evaluate the antibiotic resistance pattern of Pseudomonas aeruginosa isolated from clinical specimen and to detect Metallo beta lactamase producers as well as to accesses their biofilm forming capacity by both qualitative and quantitative analysis.  Methods: The study was conducted in Shree Birendra Hospital, Chhauni, from June to August 2025. The total of 6444 specimens was cultured and isolates of P. aeruginosa were subjected to antibiotic susceptibility tests. Metallo beta lactamase producers were identified by modified Hodge and EDTA synergy tests. Biofilm was detected by the Congo Red Agar and Microtiter Plate Assay method.Results: Out of 671 positive isolates (15.05%) from pus, urine and wound, 101 isolates of P. aeruginosa were obtained. The highest rate of distribution was observed in in-patients as well as in the age group of 61-70 years. Among the isolates, high resistance was observed against Aztreonam (65.59%) whereas isolates were most sensitive against Tobramycin (76%). 37 were found to produce Metallo beta lactamase enzyme and almost 46% were MDR. The biofilm isolates accounted for 34 by CRA but MPA detected 100 biofilm producers. The biofilm producers showed high resistance against Aztreonam (59.41%) and Levofloxacin (56.44%). Furthermore, the MBLS were the most resistant against Levofloxacin (28.7%) followed by Aztreonam (27.7%), Cefepime (27.7%), Ceftazidime (25.7%), Imipenem (25.7%) and Meropenem (25.7%). Out of all the isolates, 36 biofilm isolates were highlighted to produce MBL enzyme as well.Conclusion: Pseudomonas aeruginosa was most frequent in sputum and pus samples from inpatients and older patients, with rising resistance to monobactams, fourth-generation cephalosporins, and fluoroquinolones. High rates of MBL production and biofilm formation contributed to marked β-lactam resistance, emphasizing the need for alternative therapeutic strategies.